Adoption impact and heterogeneity of mobile agricultural advisory technologies among smallholder farmers in Nigeria - Abioye, O.; Fadare, D.A.; Omitoyin, S.A.; Ogunniyi, A.I.; Olinya, P.; Shaibu, A.; Nwilene, F.E.; Akande, A. (2025)
This paper investigates the determinants, heterogeneity, and impact of mobile agricultural technology adoption among smallholder rice farmers in Nigeria, with a focus on the RiceAdvice mobile application. Using primary data from 795 farmers in Ebonyi State, the study applies a Propensity Score Matching (PSM) framework to estimate the causal effect of adoption on productivity while addressing potential selection bias arising from non-random participation. The results show that adoption of RiceAdvice significantly increases rice yields by an average of 1,907 kg/ha compared to non-adopters, confirming the productivity-enhancing potential of mobile-based agronomic advisory tools. Adoption decisions are significantly influenced by training on RiceAdvice, access to extension services, smartphone ownership, farming experience, type of household, household size and seed entrepreneurship. The effect of age is nonlinear; adoption increases with age up to a threshold before declining. Gender-disaggregated analysis reveals nuanced heterogeneity: while men exhibit slightly higher baseline adoption probabilities, the effects of education and training substantially narrow the gender gap, suggesting that capacity-building interventions can promote gender-inclusive technology diffusion. To validate robustness, a Rosenbaum bounds sensitivity test confirms that the positive yield effects remain stable against potential endogeneity from unobserved factors. Overall, the findings demonstrate that when digital advisory services are complemented by institutional support and inclusive training, they serve as equitable tools for enhancing smallholder productivity and resilience in Nigeria’s rice sector.